If I understand you correctly, this should do it:<br><br>sums :: Num a =&gt; [[a]] -&gt; a<br>sums l = sum [sum p | p &lt;- l]<br><br>-Eric<br><br><div><span class="gmail_quote">On 2/5/07, <b class="gmail_sendername">Miranda Kajtazi
</b> &lt;<a href="mailto:mirandakajtazi@gmail.com">mirandakajtazi@gmail.com</a>&gt; wrote:</span><blockquote class="gmail_quote" style="border-left: 1px solid rgb(204, 204, 204); margin: 0pt 0pt 0pt 0.8ex; padding-left: 1ex;">
<div>Help,</div>
<div>&nbsp;</div>
<div>How to calculate the sum of list of lists in Haskell?</div>
<div>Please help me,</div><span class="sg">
<div>Miranda</div>
</span><br>_______________________________________________<br>Haskell-Cafe mailing list<br><a onclick="return top.js.OpenExtLink(window,event,this)" href="mailto:Haskell-Cafe@haskell.org">Haskell-Cafe@haskell.org</a><br>
<a onclick="return top.js.OpenExtLink(window,event,this)" href="http://www.haskell.org/mailman/listinfo/haskell-cafe" target="_blank">http://www.haskell.org/mailman/listinfo/haskell-cafe</a><br><br></blockquote></div><br>